Mechanism of action of decitabine in treating acute lymphoblastic leukemia - Gao, Xiaohui; Zeng, Hui; Sun, Fei; Zhao, Xiaoyan; Wu, Haibing; Yan, Minchao; Li, Yuan; Fu, Qinyan; Zhang, Gang (Frontiers in Medicine, 2025)
PurposeThis study aimed to evaluate the underlying mechanisms of decitabine (DAC) in inhibiting acute T-acute lymphoblastic leukemia (T-ALL) cell proliferation and promoting apoptosis.MethodsHuman T-ALL cells (CCRF-CEM) were treated with varying concentrations of DAC, and cell proliferation was assessed using a CCK-8 assay. Flow cytometry was used to detect apoptosis and cell cycle alterations. The expression levels of apoptosis-related genes, including PI3K and miR-92b-3p, were quantified using real-time PCR (RT-PCR). Western blotting was used to analyze the expression of apoptotic proteins. Furthermore, we evaluated the in vivo antileukemic activity of DAC using a nude mouse xenograft model, monitored the body weight and tumor volume of mice to calculate inhibition rates, and examined tumor morphological changes in histological sections.ResultsDAC significantly inhibited the proliferation of CCRF-CEM cells, accelerated apoptosis, and effectively downregulated the expression of PI3K, AKT, 4EBP1, and mTOR while concurrently upregulating PTEN protein expression. Its regulatory efficacy was markedly enhanced by increasing the dosage. Animal experimental results indicated that both DAC and doxorubicin substantially decreased tumor length, width, volume, and mass; however, DAC demonstrated significantly superior efficacy in inhibiting tumor growth compared to doxorubicin.ConclusionBy selectively targeting the regulation of PTEN and 4EBP1, along with their associated downstream signaling pathways, DAC effectively modulated cellular proliferation, facilitated apoptotic processes, and restrained tumor growth, providing a robust theoretical foundation for clinical treatment strategies in T-ALL.